Looking at flubromazolam metabolism from four different angles: Metabolite profiling in human liver microsomes, human hepatocytes, mice and authentic human urine samples with liquid chromatography high-resolution mass spectrometry. (May 2017) - Wohlfarth, Ariane; Vikingsson, Svante; Roman, Markus; Andersson, Mikael; Kugelberg, Fredrik C.; Green, Henrik; Kronstrand, Robert
Highlights: Comprehensive metabolism study for the new designer benzodiazepine flubromazolam. Incubation with human liver microsomes & hepatocytes and controlled administration to mice. Confirmation with 6 authentic human urine samples from forensic cases. 9 metabolites, generated by hydroxylation and/or glucuronidation ( O - and N -glucuronidation), were identified by LC–HRMS. The best analytical targets are suggested to be α-hydroxy-flubromazolam and the parent. Abstract: Flubromazolam is a triazolam benzodiazepine that recently emerged as a new psychoactive substance. Since metabolism data are scarce and good analytical targets besides the parent are unknown, we investigated flubromazolam metabolism in vitro and in vivo. 10 μmol/L flubromazolam was incubated with human liver microsomes for 1 h and with cryopreserved human hepatocytes for 5 h. Mice were administered 0.5 or 1.0 mg flubromazolam/kg body weight intraperitoneally, urine was collected for 24 h. All samples, together with six authentic forensic human case specimens, were analyzed (with or without hydrolysis, in case it was urine) by UHPLC–HRMS on an Acquity HSS T3 column with an Agilent 6550 QTOF. Data mining was performed manually and with MassMetasite software (Molecular Discovery). A total of nine metabolites were found, all generated by hydroxylation and/or glucuronidation. Besides O- glucuronidation, flubromazolam formed an N + -glucuronide. Flubromazolam was not metabolized extensively in vitro, as only two monohydroxy metabolites were detected in low intensity in hepatocytes. In the mice samples, seven metabolites were identified, which mostly matched the metabolites in the human samples. However, less flubromazolam N + -glucuronide and an additional hydroxy metabolite were observed. The six human urine specimens showed different extent of metabolism: some samples had an intense flubromazolam peak next to a minute signal for a monohydroxy metabolite, others showed the whole variety of hydroxylated and glucuronidated metabolites. Overall, the most abundant metabolite was a monohydroxy metabolite, which we propose as α-hydroxyflubromazolam based on MSMS fragmentation. These metabolism data will assist in interpretation and analytical method development.